Evidence of anthropogenic trauma in marine mammals stranded along the central California coast, 2003–2015. Issue 2 (23rd October 2017) - Barcenas‐De la Cruz, Daniela; DeRango, Eugene; Johnson, Shawn P.; Simeone, Claire A.
Abstract: A total of 11, 162 stranded marine mammals was admitted to a rehabilitation center on the central California coast between January 2003 and September 2015. Six hundred seventeen animals (6%) had evidence of anthropogenic trauma (AT). California sea lions comprised the majority (83%) of AT cases, particularly by entanglement in marine debris ( n = 277) and gunshot injuries ( n = 165). Guadalupe fur seals had the highest prevalence of entanglement in marine debris. Cetaceans were primarily affected by boat collisions ( n = 19). The highest numbers of overall strandings were recorded in 2009 ( n = 1, 690) and 2015 ( n = 1, 666); 2009 also had the highest total number ( n = 137) and prevalence (8%) of AT cases. Prevalence of fishing tackle cases increased compared to similar data from 1986 to 1998 while prevalence of gunshot cases decreased, and other causes remained static. Cases of fisheries interactions were further examined and characterized, and when direct fisheries interactions were separated from other causes of AT, fisheries interactions accounted for 50% ( n = 310) of all AT cases during the study period. Direct fisheries interactions were the most common type of AT observed among stranded marine mammals in central California. Tracking AT trends is important to further understand possible causes and inform mitigation efforts.